Digital skills between soft and hard. The Media Educator among critical issues and opportunities - Maria Luisa Iavarone; Luigi Aruta (Firenze University Press, 2022)
This era is marked by a profound mutation in the forms and expression of human life that reflects a substantial alteration of the traditional coordinates of space and time, axes of thought con-fused into a third dimension imposed by the digital environment: immediacy. This transition implies a reflection on educational potential of technologies in response to contemporary emergencies and fragilities. Therefore, in this historical-cultural context, it might be appropriate to rethink digital skills no longer as hard skills, i.e., as mere technical-computational skills, but as soft skills, i.e., cognitive-operational skills, , indispensable for inhabiting in onlife era. Hence, the need to have Media Educators with a strong educative and cultural, as well as technological, identity, who know how to operate especially in the non-formal and informal sphere, in the third sector and in the territories of risk, moving effectively and efficiently, between criticalities and opportunities, in the living platforms of digital, a potential place for the development of digital soft skills.   Le digital skills tra soft e hard. L'Educatore Mediale tra criticità e opportunità. L'epoca che viviamo sembra attraversata da una profonda mutazione nelle forme e nell'espressione della vita umana che riflettono una sostanziale alterazione delle coordinate tradizionali di spazio e tempo, assi del pensiero con-fusi in una terza dimensione imposta dall'ambiente digitale: l'istantaneità. Questa transizione implica una riflessione circa le potenzialità educative delle tecnologie in risposta alle emergenze e alle fragilità contemporanee. Quindi, in questo contesto storico-culturale, potrebbe essere opportuno ripensare le competenze digitali non più come hard skills, ossia come mere abilità di natura tecnico-computazionale, bensì come soft skills, ossia abilità cognitivo-operazionali, indispensabili per abitare in epoca onlife. Di qui, la necessità di disporre di Educatori Mediali con una forte identità educativo-culturale, oltre che tecnologica, che sappiano operare soprattutto in ambito non formale e informale, nel terzo settore e nei territori del rischio, muovendosi con efficacia ed efficienza, tra criticità e opportunità, nelle piattaforme abitative del digitale, potenziale luogo di sviluppo delle digital soft skills.